EuCoMeS 2018 Proceedings of the 7th European Conference on Mechanism Science - Corves, Burkhard; Wenger, Philippe; Hüsing, Mathias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents the latest academic research and industrial applications in the area of mechanisms, robotics and dynamics. Contributions cover such topics as biomedical applications, control issues of mechanical systems, dynamics of multi-body systems, experimental mechanics, haptic systems, history of mechanism science, industrial and non-industrial applications, linkages and cams, mechanical transmissions and gears, mechanics of robots and manipulators, theoretical kinematics. Resulting from the 7th European Conference on Mechanism Science, which was held at RWTH Aachen University on September 4-6, 2018, this works comprises an overview on current research activities across Europe.
Keywords: Control engineering; Robotics; Automation; Multibody systems; Vibration; Mechanics, Applied; Machinery; Control, Robotics, Automation; Multibody Systems and Mechanical Vibrations; Machinery and Machine Elements